Is there a size-induced market failure in skills training? - Paul Vandenberg; Long Q. Trinh (Asian Development Bank Institute (ADBI), 2016)
A skilled and educated workforce can support the competitiveness of enterprises of all sizes. However, smaller firms may face greater challenges in developing human capital. We explore differences between smaller and larger firms in offering skills training and in hiring workers with more formal education. Drawing on a dataset of enterprises in five Asian countries, we find major size-based differences in education and training. While smaller firms train less, they also are less inclined to view an inadequately skilled workforce as a major constraint on their operations. It may be that smaller firms are content to occupy niches in a low-skills equilibrium. Our empirical results do offer the possibility, however, that a size-induced market failure in skills training may coexist with a lower regard for skills. The policy implications are not only that governments can reduce the costs for firms to train, but also that micro and small firms need to be sensitized to the benefits of skills upgrading.
Keywords: I25; M21; O1; 330; Small and medium-sized enterprises; SMEs; market failure; skills training; skills upgrading; skilled workforce; human capital